Characterization of novel yeasts that ferment lactose in cheese whey - Delshadi, Rana (University of Wisconsin--Stout, 2019)
Cheese whey offers a potential carbon source for ethanol production since it is rich in lactose. Yeast species such as Kluyveromyces marxianus can produce ethanol from whey. Here, we enriched for and screened wild yeast strains for their ability to ferment the lactose in whey with the goal of providing new species for industrial adoption. We characterized 11 strains capable of growing on galactose and lactose under mildly acidic conditions. Of these, we chose 3 yeast strains capable of producing gas and lowering the pH. Their fermentation ability was compared to the known fermenters Saccharomyces cerevisiae and K. marxianus. Lactose concentrations decreased while ethanol yield increased for S. cerevisiae and cultivated strain 1-TENH-1 grown in whey containing 25% lactose. In contrast, K. marxianus and cultivated strains 3-RMLT-1 and RM-3 showed higher ethanol production in 12%-lactose whey. The maximum ethanol concentration attained was 12%, produced by S. cerevisiae grown in 25% lactose, compared to 2.9% by 1-TENH-1 in the same medium. Although we cultivated wild K. marxianus strains capable of producing ethanol from lactose, the ethanol yield was relatively low compared to S. cerevisiae. These results suggest that although wild yeasts and K. marxianus are capable of ethanol production, S. cerevisiae is more economically feasible.
Keywords: Yeast; Lactose; Cheese; Whey